Preventing Childhood Obesity through Physical Activity - Linda Bobroff (EDIS)
“Many parents are concerned about rising rates of childhood obesity. It’s important to keep a healthy perspective on the situation and not overreact with overly restrictive approaches that can do more harm than good. One way to promote healthy weights in children is to help them to be physically active.” This 2-page Family Album Radio transcript was written by Linda Bobroff and published by the UF Department of Family, Youth and Community Sciences, September 2012.